Respuesta :

1)

[tex]f(x) = 2x - 5\\f(4) = 2(4) - 5 = 8 - 5 = 3[/tex]

2)

[tex]f(x) = 2x - 5\\f(-6) = 2(-6) - 5 = -12 - 5 = -17[/tex]

3)

[tex]g(x) = x + 3\\g(8) = 8 + 3 = 11[/tex]

4)

[tex]h(x) = 4x\\h(5) = 4 \cdot 5 = 20[/tex]

5)

[tex]k(x) = x^2 + 2x - 5\\k(6) = 6^2 + 2 \cdot 6 - 5 = 36 + 12 - 5 = 43[/tex]

6)

[tex]k(x) = x^2 + 2x - 5\\k(-3) = (-3)^2 + 2(-3) - 5 = 9 - 6 - 5 = -2[/tex]

7)

[tex]g(x) = x + 3\\g(3x) = 3x + 3 = 3(x + 1)[/tex]

8)

[tex]f(x) = 2x - 5\\f(4x) = 2(4x) - 5 = 8x - 5[/tex]

9)

[tex]h(x) = 4x\\h(5t) = 4(5t) = 20t[/tex]

10)

[tex]k(x) = x^2 + 2x - 5\\k(4t) = (4t)^2 + 2(4t) - 5 = 16t^2 + 8t - 5[/tex]

11)

[tex]f(x) = 2x - 5\\f(x + 3) = 2(x + 3) - 5 = 2x + 6 - 5 = 2x + 1[/tex]

12)

[tex]f(x) = 2x - 5\\g(x) = x + 3\\f(g(x)) = 2(x + 3) - 5 = 2x + 6 - 5 = 2x + 1[/tex]